THE INFLUENCE OF GEOGRAPHY EDUCATION ON STUDENTS' UNDERSTANDING OF THE ROLE OF TOLI-TOLI COASTAL VEGETATION IN MAINTAINING SOIL STABILITY - Ismiatus, Wilda; Hadi, Bambang Syaeful (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
Geography education is crucial in fostering students’ ecological awareness, particularly regarding coastal ecosystems. This study examined the effect of geography education on students’ understanding of coastal vegetation functions in maintaining soil stability in Toli-Toli. Using a quantitative explanatory design and simple linear regression, data were collected via a 4-point Likert scale questionnaire covering geography education and ecological understanding indicators. The analysis showed a significant effect of geography education, with a partial t-test (t = 11.979 > 1.983; p = 0.001) and F-test (F = 143.492 > 3.09; p < 0.001). The determination coefficient (R² = 0.589) revealed that geography education accounts for 58.9% of the variance in students’ understanding. These results highlight the importance of contextual and applied geography learning to strengthen ecological literacy, enabling students to appreciate the ecological and socio-economic roles of coastal vegetation, particularly mangroves, in protecting coastlines and maintaining environmental sustainability. Keywords: Geography Education, Ecological Awareness, Coastal Vegetation